An explanatory framework of palm oil panic buying behavior in Indonesia: Do perceived scarcity and perceived price being enablers? - Meuthia; Ratni Prima Lita; Rini Rahmahdian (Cogent Business & Management, 2023)
This study aims to analyze the main effect of perceived scarcity and perceived price on the panic buying behavior of palm oil in Indonesia. Perceived control and consumer anger also investigate as consequences of perceived scarcity. This study uses explanatory research quantitative analysis techniques with hypothesis testing. The sampling technique of non-probability sampling is done through the convenience sampling method. The sample in this study was 289 consumers of palm oil in West Sumatra, Indonesia, which were collected by distributing online questionnaires via the link of google form. SmartPLS 3.0 tests the effect between the variables analyzed on the first-order level construct. The results show that perceived scarcity does not show a significant direct effect on panic buying behavior, but it does affect perceived control and consumer anger, which in turn affect panic buying behavior. Panic buying behavior is also influenced by perceived price. Briefly, the results of this study have practical and conceptual implications which provide valuable insight for further research.
Keywords: 650; Consumer Anger; Panic Buying Behavior; Perceived Control; Perceived Price; Perceived Scarcity; Smartpls 3.0